A prototype pixel readout chip working in single photon counting mode with a novel charge sharing suppression scheme. (1st July 2022) - Cui, S.; Wei, W.; Zhang, J.; Li, M.; Li, H.; Li, Z.; Jiang, X.; Zhu, K.; Liu, P.; Wang, Z.; Chen, Y.
Abstract: Spectral distortion due to the charge sharing effect becomes a severe issue in single-photon counting pixel detectors. The HEPS-BPIX4 prototype chip, dedicated for the HEPS in China, implements a novel architecture to mitigate charge sharing and permit spectroscopic imaging with high efficiency. In the architecture, a central pixel communicates with others in a cluster of 3 × 3 pixels. The algorithm simulation showed a charge sharing elimination accuracy better than 90%. The prototype chip has been designed in a 130 nm CMOS technology. The preliminary measurements show a charge gain of 48 mV/ke − and an equivalent noise charge of 150 e − rms. Detailed tests in a 4 × 4 pixel array for the charge sharing are performed using electrical test pulses. The hit allocation in the core four adjacent pixels of the array indicates that effective suppression of charge sharing has been realized.